Remittances and Natural Disasters : Ex-post Response and Contribution to Ex-ante Preparedness - Mohapatra, Sanket (2012)
Macro- and micro-economic evidence suggests a positive role of remittances in preparing households against natural disasters and in coping with the loss afterwards. Analysis of cross-country macroeconomic data shows that remittances increase in the aftermath of natural disasters in countries that have a larger number of migrants abroad. Analysis of household survey data in Bangladesh shows that per capita consumption was higher in remittance-receiving households than in others after the 1998 flood. Ethiopian households that receive international remittances seem to rely more on cash reserves and less on selling household assets or livestock to cope with drought. In Burkina Faso and Ghana, international remittance-receiving households, especially those receiving remittances from high-income developed countries, tend to have housing built of concrete rather than mud and greater access to communication equipment, suggesting that they are better prepared against natural disasters.